2020
DOI: 10.1007/s12182-020-00518-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium–osmium (Re–Os) geochronology of crude oil from lacustrine source rocks of the Hailar Basin, NE China

Abstract: Re–Os radiometric dating of crude oil can be used to constrain the timing of hydrocarbon generation, migration or charge. This approach has been successfully applied to marine petroleum systems; however, this study reports on its application to lacustrine-sourced natural crude oils. Oil samples from multiple wells producing from the Cretaceous Nantun Formation in the Wuerxun-Beier depression of the Hailar Basin in NE China were analysed. Subsets of the Re–Os data are compatible with a Cretaceous hydrocarbon ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…across the basin would not only provide independent age controls for the corresponding magnetostratigraphy studies but also bring detailed constraints on the potential diachronicity of the units inside the basin. Fourth, Re-Os geochronometry has been widely used as a proxy for determining precise and accurate depositional ages of marine organic-rich rocks (Rooney et al, 2020;Selby and Creaser, 2003;Tripathy et al, 2015) and is now successfully applied to similar deposits in lacustrine nonmarine systems (Cumming et al, 2012;Cumming et al, 2014;Meng et al, 2020). As the largest petroliferous basin in the Tibetan plateau, the Qaidam basin contains abundant rocks that are rich in organic matter, especially the lacustrine source rocks in the Xiaganchaigou Fm.…”
Section: Future Perspectivementioning
confidence: 99%
“…across the basin would not only provide independent age controls for the corresponding magnetostratigraphy studies but also bring detailed constraints on the potential diachronicity of the units inside the basin. Fourth, Re-Os geochronometry has been widely used as a proxy for determining precise and accurate depositional ages of marine organic-rich rocks (Rooney et al, 2020;Selby and Creaser, 2003;Tripathy et al, 2015) and is now successfully applied to similar deposits in lacustrine nonmarine systems (Cumming et al, 2012;Cumming et al, 2014;Meng et al, 2020). As the largest petroliferous basin in the Tibetan plateau, the Qaidam basin contains abundant rocks that are rich in organic matter, especially the lacustrine source rocks in the Xiaganchaigou Fm.…”
Section: Future Perspectivementioning
confidence: 99%
“…Additionally, studies of natural systems and hydrous pyrolysis experiments have shown that Re and Os are transferred from source rocks to bitumen to oil without significant fractionation, and without significantly affecting Re-Os systematics and Os isotopic composition of the source rock (Selby et al, 2007;Finlay et al, 2012;Rooney et al, 2012;Cumming et al, 2014). Accordingly, the Re-Os geochronometer and Os isotope fingerprinting have shown promising potential both for dating crude oils in marine and lacustrine petroleum systems and for correlating oils to their source rocks Finlay et al, 2011;Lillis and Selby, 2013;Cumming et al, 2014;Georgiev et al, 2016;2019;Ge et al, 2018;Liu et al, 2018;Corrick et al, 2019;Scarlett et al, 2019;Meng et al, 2021). However, it remains uncertain exactly which event is being dated.…”
Section: Introductionmentioning
confidence: 99%